2023
DOI: 10.1101/2023.02.10.528004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The yeast RNA methylation complex consists of conserved yet reconfigured components with m6A-dependent and independent roles

Abstract: N6-methyladenosine (m6A), the most abundant mRNA modification, is deposited in mammals/insects/plants by m6A methyltransferase complexes (MTC) comprising a catalytic subunit and at least five additional proteins. The yeast MTC is critical for meiosis and was known to comprise three proteins, of which two were conserved. We uncover three novel MTC components (Kar4/Ygl036w-Vir1/Dyn2). All MTC subunits, except for Dyn2, are essential for m6A deposition and have corresponding mammalian MTC orthologs. Unlike the ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…Recent works showed that the yeast MTC contains three additional subunits (Kar4, Ygl036w/Vir1 and Dyn2). Furthermore, the new analysis showed that the yeast MTC is much more conserved than previously anticipated (Ensinck et al, 2023; Park, Belnap, et al, 2023; Park, Sporer, et al, 2023). Briefly, Kar4 was identified as the METTL14 orthologue.…”
Section: The Yeast Mtc Is Conserved With Distinct Featuresmentioning
confidence: 74%
See 4 more Smart Citations
“…Recent works showed that the yeast MTC contains three additional subunits (Kar4, Ygl036w/Vir1 and Dyn2). Furthermore, the new analysis showed that the yeast MTC is much more conserved than previously anticipated (Ensinck et al, 2023; Park, Belnap, et al, 2023; Park, Sporer, et al, 2023). Briefly, Kar4 was identified as the METTL14 orthologue.…”
Section: The Yeast Mtc Is Conserved With Distinct Featuresmentioning
confidence: 74%
“…Budding yeast was one of the first models used to show that m6A has an important function (Bodi et al, 2010; Clancy, 2002). The IME4 gene (Inducer of Meiosis 4), which encodes the sole m6A methyltransferase in budding yeast and is orthologous to METTL3 in humans, is not essential for viability and acts specifically in the early phases of meiosis (Agarwala et al, 2012; Ensinck et al, 2023; Schwartz et al, 2013). The tight regulation of m6A deposition during early meiosis in budding yeast contrasts that in higher eukaryotes, where m6A is constitutively and by default deposited (Dominissini et al, 2012; Uzonyi et al, 2023).…”
Section: Budding Yeast and Fission Yeast Have Different M6a Methyltra...mentioning
confidence: 99%
See 3 more Smart Citations